P-90 Implementation of research into hospices through community of influence: crn west midlands model. Issue Volume 7:Issue (2017)Supplement 2 (1st November 2017) - Prew, Sandra; Evans, Marion; Burt, Rebecca; Machin, Julie; Marlow, Clare; Shilton, Andrea; Salter, Ami; Young, Annie; Phipps, Marie; Shepley, Hilary
Abstract : There is a need to provide high quality, evidence-based supportive and palliative care research. However, recruitment to supportive and palliative care research studies remains a challenge. Therefore, more research evidence is required in this specialty. The supportive and palliative care research model aims to: Improve care through research, increase awareness of research within the West Midlands and share nationally Support local hospices and care homes to become involved in research Encourage clinicians to identify topics for future research, to be adopted onto the National Research Portfolio, and ensure that researchers in the area are able to offer access to studies for participants in all areas. Progress and achievements to date include: contributing to the delivery of existing National Institute for Health Research Portfolio studies by carrying out site initiation visits and assisting with study recruitment. generating new studies that are running in the West Midlands (WM) through the WM Collaborative Actioning Research in End of Life and Supportive Care (WMCARES). sharing research priority topics identified following a survey of hospices in the West Midlands and to investigate in the near future. increasing our visibility across the West Midlands to promote and share our strategy. This has involved talks with local radio, West Midlands partner organisations, other Clinical Research Networks and primary care organisations. bringing together an enthusiastic and committed workforce of diverse healthcare professionals, including clinical research speciality and sub-specialty leads, a nursing team, locality manager, administrative staff, research delivery and portfolio managers. Our next planned steps include short and long term goals. Highlights include: Enhanced IT systems, develop a Health Research Authority flow diagram and create a Supportive and Palliative Care Nurse Forum with collaboration with CRN West Midlands.